Long-Term Evolution of the Hip and Proximal Femur after Hip Reconstruction in Non-Ambulatory Children with Cerebral Palsy: A Retrospective Radiographic Review - Norine Ma; Peter Tischhauser; Carlo Camathias; Reinald Brunner; Erich Rutz (MDPI AG, 2022)
Background: Hip displacement in children with cerebral palsy (CP) has a higher prevalence in non-ambulatory children. Progression can lead to pain, pelvic obliquity and difficulty with sitting. This can be addressed with hip reconstruction. Our study aims to report the long-term radiological outcomes after hip reconstruction, in particular the evolution of femoral head deformity. Methods: A total of 58 hips of non-ambulatory children with CP were evaluated retrospectively using pre-operative, early (median 120 days) and late post-operative (median 8.6 years) anteroposterior standardised radiographs. All the hips were treated with femoral shortening varus derotation osteotomy (VDRO), pelvic osteotomy and an open reduction, if indicated. The radiographical indices measured included the migration percentage (MP), sharp angle, acetabular index, centre-edge angle, neck shaft angle, head shaft angle, pelvic obliquity, femoral head sphericity, femoral head deformity (FHD) and growth plate orientation. Results: Improvements in hip congruency and morphology were evident after reconstructive hip surgery. These were maintained at the late post-operative time point. Median MP improved from 56% (IQR 46-85%) to 0% (IQR 0-15%) at early follow-up. This increased to 12% (IQR 0-20%) at late follow-up. Pre-operatively, FHDs of 14 hips (24%) were classified as grade A (spherical femoral head). This increased to 22 hips (38%) at early follow-up and increased further to 44 hips (76%) at late follow-up. Conclusions: Our study shows that hip reconstruction reduces hip displacement in the long term, indicated by decreased post-operative MP maintained at long-term follow-up. Although non-ambulatory children lack weight-bearing forces promoting bone remodelling, improved femoral head morphology after surgery alters the forces between the acetabulum and the femoral head. Mild femoral head deformity (grades A and B) remained stable and even improved after surgery, postulated to be due to severe osteoporosis allowing remodelling.